HYDROALCOHOLIC EXTRACT OF MATRICARIA CHAMOMILLA LINN. AMELIORATES LIPIDS, LIPOPROTEINS, AND PARAOXONASE IN ISOPROTERENOL-INDUCED MYOCARDIAL INFARCTION IN WISTAR RATS - VADIVELAN RAMACHANDRAN; GAUTAM ADHIKARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate the effect of the hydroalcoholic extract of Matricaria Chamomilla Linn. (CHAE) on lipids, lipoproteins, and antioxidants activity in isoproterenol (ISO)-induced myocardial infarcted rats. Methods: ISO (85 mg/kg, s.c.)-induced myocardial infarction for 2 consecutive days at an interval of 24 h. Rats were pretreated with CHAE (100 and 200 mg/kg, oral) for a period of 20 days and ISO was injected on 21 and 22 days at 24 h intervals and after 24 h, blood was collected through retro-orbital plexus for the estimation of lipids, lipoproteins, and antioxidants assay. Results: In the present study, ISO caused a significant increase in the concentration of total cholesterol, triglycerides, low-density lipoprotein cholesterol (LDL-C), very LDL-C, and lipid peroxidation whereas a significant decrease in the concentration of high-density lipoprotein-C. ISO administration also significantly decreased the activities of paraoxonase (PON) enzyme. Oral pre-treatment of CHAE at doses of 100 and 200 mg/kg body weight (bw) for 20 days challenged with a concurrent injection of ISO (85 mg/kg bw) on 21 and 22 days significantly attenuated these alterations and restored the levels of lipids and lipoproteins. In addition, CHAE significantly elevated the serum antioxidants enzyme PON and catalase (CAT). Conclusion: The report revealed that pre-treatment with CHAE ameliorated lipid and lipoprotein and increased the antioxidant PON and CAT activity and decreased LPO level in ISO-treated male albino Wistar rats.